Management of an Extrusive Luxation Concomitant with Subluxation: A Case Report with Ten-Year Follow-Up - Saeedeh Mokhtari; Sepideh Hosseini; Maryam Khosrozadeh (Case Reports in Dentistry)
Traumatic dental injuries (TDIs) are a public health concern with high prevalence and incidence rates. Proper intervention can significantly reduce the subsequent complications of these events. This case report describes the clinical interventions to manage a patient with traumatized maxillary incisor with severe extrusive luxation. The procedure was aimed at preserving pulp vitality and providing periodontal maintenance to the highest possible degree. Owing to timely and accurate treatments, ten years of success have been achieved in this patient, as discussed in this case report.